Search for maximal flavor violating scalars in same-charge lepton pairs in pp collisions at sqrt[s]=1.96 TeV. - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2009)
Models of maximal flavor violation (MxFV) in elementary particle physics may contain at least one new scalar SU(2) doublet field Phi(FV)=(eta(0),eta(+)) that couples the first and third generation quarks (q_(1), q_(3)) via a Lagrangian term L(FV)=xi(13)Phi(FV)q(1)q(3). These models have a distinctive signature of same-charge top-quark pairs and evade flavor-changing limits from meson mixing measurements. Data corresponding to 2 fb(-1) collected by the Collider Dectector at Fermilab II detector in pp[over ] collisions at sqrt[s]=1.96 TeV are analyzed for evidence of the MxFV signature. For a neutral scalar eta(0) with m_(eta;(0))=200 GeV/c(2) and coupling xi(13)=1, approximately 11 signal events are expected over a background of 2.1+/-1.8 events. Three events are observed in the data, consistent with background expectations, and limits are set on the coupling xi(13) for m(eta(0)=180-300 GeV/c(2).